Bony Stroke: Ischemic Stroke Caused by Mechanical Stress on Brain Supplying Arteries From Anatomical Bone or Cartilage Anomalies. Issue 5 (13th April 2023) - Haertl, Johanna; Renz, Martin; Wunderlich, Silke; Hemmer, Bernhard; Hofauer, Benedikt; Gempt, Jens; Kallmayer, Michael; Boeckh-Behrens, Tobias; Kirschke, Jan S.; Ikenberg, Benno David
Abstract : Background: Bone or cartilage anomalies with affection of brain supplying arteries are a potential structural cause for ischemic stroke. In the following, we termed this entity bony stroke. Due to rarity of their description, there is no standardized workup and therapy for bony strokes. Methods: Retrospectively, we extracted diagnostic and therapeutic workup of all patients considered to have had a bony stroke between January 2017 to March 2022 at our comprehensive care center. Results: In total, 6 patients classified as a bony stroke were identified among 4200 acute patients with ischemic stroke treated during the study period. Each patient had recurrent ischemic strokes in the dependent vascular territory before diagnosis. Diagnosis was achieved by a combination of imaging devices, including sonography, computed tomography, and magnetic resonance imaging. In addition to conventional static imaging, the application of dynamic imaging modalities with the patients' head in rotation or reclination confirmed a vessel affection following head movements in 3 patients (50%). Treatment options were interdisciplinary assessed and included the following: conservative treatment (n=1), endovascular stenting (n=2) or occlusion (n=2), surgical removal of bone/ cartilage (n=2), and surgical bypass treatment (n=1). In follow-up (mean 11.7 months), no patient experienced further ischemia. Conclusions: As a differential diagnosis, bony strokes may be considered in patients with recurrent ischemic stroke of unknown cause in one dependent vascular territory. Interdisciplinary evaluation and treatment may eliminate risk of stroke recurrence.